MR SER: PHOTOMETRIC PORTRAIT OF UNUSUAL POLAR - Baklanov, A. V.; Pavlenko, E. P. (Одеські астрономічні публікації, 2017)
Based on the CCD photometry (R) of MR Ser obtained in 1999-2001, the period was corrected with a corresponding ephemeris Min.HJD = 2451369.9664 + 0.0787966E. The phase curve exhibits drastic changes with luminosity.